EDUCATION STANDARDS OF PERM NATIONAL RESEARCH POLYTECHNIC UNIVERSITY: CONCEPT OF DEVELOPMENT AND EXPERIENCE IN DESIGN - Michail B. Gitman; Valery Yu. Stolbov; Alexandr N. Danilov; Nikolay V. Lobov (Высшее образование в России)
Specialists training at national research universities requires creation of selfG dependently established educational standards, which differ essentially from the Federal Standards in complexity, structure, content, conditions of implementation, as well as applyingof special educational technologies. Education standards for each university must have their own peculiarities. The authors present the concept of development and the experience in design of own education standards of Perm National Research Polytechnic University. These education standards provide formation of innovation competence of technical specialists.